1991
DOI: 10.1002/bjs.1800780435
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of honey in treatment of burns

Abstract: A total of 104 cases of superficial burn injury were studied to assess the efficiency of honey as a dressing in comparison with silver sulfadiazine gauze dressing. In the 52 patients treated with honey, 91 per cent of wounds were rendered sterile within 7 days. In the 52 patients treated with silver sulfadiazine, 7 per cent showed control of infection within 7 days. Healthy granulation tissue was observed earlier in patients treated with honey (mean 7.4 versus 13.4 days). Of the wounds treated with honey 87 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
1
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(183 citation statements)
references
References 12 publications
2
172
1
8
Order By: Relevance
“…Hamdy et al reported that the number of microorganisms and bacterial species decreased by 50-100 % by application of honey on chronic infected wounds [17]. Various authors reported mild or no pain at all during dressing change with honey as compared to other treatments [12,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Hamdy et al reported that the number of microorganisms and bacterial species decreased by 50-100 % by application of honey on chronic infected wounds [17]. Various authors reported mild or no pain at all during dressing change with honey as compared to other treatments [12,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Mean time to healing was 32 days in the honey-treated group and 18.4 days in the comparison group (WMD 13.6 days, 95% CI 10.02-17.18 days), significantly favouring early excision and skin grafting [7]. Honey compared with silver sulfadiazine did not reveal significant difference between these two interventions (WMD -4.37 days, 95% CI -8.94 to 0.19 days) [8].…”
Section: The Methodologist's Point Of Viewmentioning
confidence: 84%
“…On the other hand, clinical trials established that floral origin and antibacterial potency of honey do not seem to correlate with any difference in effectiveness in the therapy of burns [41]. It was noted that applying honey determines a reduction in inflammation and scar contractures.…”
Section: The Anti-infectious Activity Of Honeymentioning
confidence: 99%
“…It was noted that applying honey determines a reduction in inflammation and scar contractures. Antioxidant effect of honey in neutralizing free radicals, together with antibacterial action, low pH, high viscosity, hygroscopic effect and moist environment, all contribute to the efficiency of honey in burns treatment [41,42].…”
Section: The Anti-infectious Activity Of Honeymentioning
confidence: 99%